PENERAPAN MARKETING MIX SEBAGAI STRATEGI DALAM TARGET PASAR POLITIK GENERASI MILLENIAL - Putu R Adwishanty (Jurnal Ilmu dan Budaya, 2019)
The First  is the marketing politics using marketing mix or marketing mix known as 4P, product, promotion, price and place. This article will discuss the marketing politics  as the millennials generation. Political marketing has been used as a winning strategy. Many of these strategies have their own to be well received by the public. Marketing concepts adapted in politics used to improve the efficiency and effectiveness of ideological transfers and work programs, from contestants to the public in a campaign.